Utilization of Online Mobile Phone Applications for Diagnosis and Evaluation of Quality of Life in Allergic Rhinitis Patients - Tri Wahyuliati; Eva Nur Fadila; Asti Widurui; Imam Marzuki (Proceedings International Conference on Sustainable Innovation (ICoSI), 2021)
Chronic rhinitis is inflammation of the nasal mucosa for more than 12 weeks. The prevalence of rhinitis in Indonesia has reached 12.4% and will continue to increase. Chronic rhinitis can affect quality of life, especially daily activities and sleep disorders. This study aims to determine the correlation of the Score for Allergic Rhinitis (SFAR) with the quality of life of sufferers. This research was conducted using observational analytical methods, namely a cross sectional design. The samples used were 46 samples with predetermined inclusion and exclusion criteria. The research instrument uses a quality-of-life questionnaire in the form of statements and Visual Analog Scales (VAS). Data analysis used Shappiro-Wilk for the normality test and contingency coefficient test to determine the correlation between variables. The research results showed a significant correlation between the Score for Allergic Rhinitis and the quality of life of chronic rhinitis sufferers (p=0.000). This correlation relationship has one direction and moderate strength (r=0.567). The highest quality of life statement, namely 52.17% of respondents, stated that rhinitis complaints would decrease after using medication/nasal spray. And for the VAS parameters, the results showed that the highest number given was 0 for 45.65% of students, which means they did not feel any pain.